Using Machine Learning Algorithms to Predict Immunotherapy Response in Patients with Advanced Melanoma - Johannet, Paul; Coudray, Nicolas; Donnelly, Douglas M.; Jour, George; Illa-Bochaca, Irineu; Xia, Yuhe; Johnson, Douglas B.; Wheless, Lee; Patrinely, James R.; Nomikou, Sofia; Rimm, David L.; Pavlick, Anna C.; et al. (Clinical cancer research, 2021)
Several biomarkers of response to immune checkpoint inhibitors (ICI) show potential but are not yet scalable to the clinic. We developed a pipeline that integrates deep learning on histology specimens with clinical data to predict ICI response in advanced melanoma. We used a training cohort from New York University (New York, NY) and a validation cohort from Vanderbilt University (Nashville, TN). We built a multivariable classifier that integrates neural network predictions with clinical data. A ROC curve was generated and the optimal threshold was used to stratify patients as high versus low risk for progression. Kaplan-Meier curves compared progression-free survival (PFS) between the groups. The classifier was validated on two slide scanners (Aperio AT2 and Leica SCN400). The multivariable classifier predicted response with AUC 0.800 on images from the Aperio AT2 and AUC 0.805 on images from the Leica SCN400. The classifier accurately stratified patients into high versus low risk for disease progression. Vanderbilt patients classified as high risk for progression had significantly worse PFS than those classified as low risk ( = 0.02 for the Aperio AT2; = 0.03 for the Leica SCN400). Histology slides and patients' clinicodemographic characteristics are readily available through standard of care and have the potential to predict ICI treatment outcomes. With prospective validation, we believe our approach has potential for integration into clinical practice.